Numerical simulation of magnetically driven nanomaterial rotating flow configured by convective-radiative cone with chemical reaction - Cyrus Raza Mirza; Muhammad Salman Kausar; Muhammad Nasir; M. Waqas; Nurnadiah Zamri; Iskandar Shernazarov; S.U. Khan; Nidhal Ben Khedher (Chemical Engineering Journal Advances)
Indeed, nanoliquids have acquired substantial consideration in heat transference field because of their inimitable thermal attributes and favorable application likelihoods. In contrast to orthodox liquids, the haphazard movement of nanoparticles within nanoliquid strengthens fluid turbulence, accomplishes superior thermal effectiveness and declines thermal resistance. Nanoliquids have ample utilization, for illustration, solar energy, electronic chips, automotive radiators and heat exchangers etc. This communication reports chemically reactive electro-magnetized nanomaterial dissipative flow confined by rotating cone. Flow expressions include thermo-solutal buoyancy, varying viscosity and magneto-hydrodynamics. Radiative heat, thermophoresis, viscous dissipation, Brownian diffusion, thermal source and first order chemical reaction are pondered to model transport expressions. Relevant variables are introduced to transfigure partial differential mathematical expressions to mathematical ordinary ones. Numerical outcomes for non-dimensional mathematical expressions are reported via bvp4c algorithm in MATLAB. The comprehensive results featuring dimensionless quantities are explored through graphs and arithmetic representations. It is evaluated that escalating values of variable viscosity, Prandtl number and unsteady parameter decline temperature but temperature is improved as a consequence of progressive variation in radiation parameter, Eckert number, thermophoresis parameter, heat generating and Brownian diffusive variables. The study is relevant to cooling industry, electroconductive, thermal collector and nano-materials processing.